Melatonin in Newborn Infants Undergoing Surgery: A Pilot Study on Its Effects on Postoperative Oxidative Stress - Serafina Perrone; Carmelo Romeo; Lucia Marseglia; Sara Manti; Cristina Rizzo; Silvia Carloni; Maria Cristina Albertini; Walter Balduini; Giuseppe Buonocore; Michael D. Weiss; Eloisa Gitto (MDPI AG, 2023)
Surgery is frequently associated with excessive oxidative stress. Melatonin acts as an antioxidant and transient melatonin deficiency has been described in neonatal surgical patients. This randomized, blinded, prospective pilot study tested the hypothesis that oral melatonin supplementation in newborn infants undergoing surgery is effective in reducing perioperative oxidative stress. A total of twenty-three newborn infants requiring surgery were enrolled: 10 received a single dose of oral melatonin 0.5 mg/kg in the morning, before surgery (MEL group), and 13 newborns served as the control group (untreated group). Plasma concentrations of melatonin, Non-Protein-Bound Iron (NPBI), Advanced Oxidation Protein Products (AOPP), and F2-Isoprostanes (F2-IsoPs) were measured. Both in the pre- and postoperative period, melatonin concentrations were significantly higher in the MEL group than in the untreated group (preoperative: 1265.50 ± 717.03 vs. 23.23 ± 17.71 pg/mL, p < 0.0001; postoperative: 1465.20 ± 538.38 vs. 56.47 ± 37.18 pg/mL, p < 0.0001). Melatonin significantly increased from the pre- to postoperative period in the untreated group (23.23 ± 17.71 vs. 56.47 ± 37.18 pg/mL; pg/mL p = 0.006). In the MEL group, the mean blood concentrations of NPBI, F2-IsoPs, and AOPP significantly decreased from the pre- to the postoperative period (4.69 ± 3.85 vs. 1.65 ± 1.18 micromol/dL, p = 0.049; 128.40 ± 92.30 vs. 50.25 ± 47.47 pg/mL, p = 0.037 and 65.18 ± 15.50 vs. 43.98 ± 17.92 micromol/dL, p = 0.022, respectively). Melatonin concentration increases physiologically from the pre- to the postoperative period, suggesting a defensive physiologic response to counteract oxidative stress. The administration of exogenous melatonin in newborn infants undergoing surgery reduces lipid and protein peroxidation in the postoperative period, showing a potential role in protecting babies from the deleterious consequences of oxidative stress.